New Pedagogical Technologies in Teaching the Russian Language (Eurasian Research Bulletin, 2022)
One of the main tasks of teaching the Russian language is not only to give knowledge to students, but also to awaken a personal motive, instill interest in the subject, develop a desire for speech self-improvement.